Identification and prioritization of issues to implementation of information-facilitated product recovery system for a circular economy - Ashish Dwivedi; Dindayal Agrawal; Jitender Madaan (Modern Supply Chain Research and Applications, 2020)
Purpose Information-facilitated product recovery system (IFPRS) has captivated industry attention and has developed into a matter of consideration among the researchers because of enhanced climate concerns, jurisdictive logics and societal liabilities. Although IFPRS implementation has become an essential aspect in manufacturing industries functional in the developed nations, still, limited consideration has been given in the literature to analyze the issues to IFPRS implementation for a circular economy (CE) in emerging and developing nations. Therefore, the objective of this study is to recognize issues to implementing IFPRS for a CE in context of select manufacturing industries in India. Design/methodology/approach In this study, 24 potential issues are established from the literature and from suggestions from the experts. The issues are clubbed under five different perspectives of technical, government, organization, policy and knowledge. Further, fuzzy VIKOR technique is applied on the results obtained to prioritize the identified issues. A sensitivity analysis has been carried out to check the robustness of the framework. Findings The present study shows that lack of skills and expertise in IFPRS implementation for a CE (I2), deficient capital to implement a CE in IFPRS (I9), inadequate in adopting recent IT technology (I18), feasibility of IFPRS employment for a CE (I6) and no efficient training and program to CE adoption (I21) are the top five potential issues in implementing IFPRS practices for a CE in Indian manufacturing industries. Research limitations/implications In literature, limited study has been observed on determining issues to implementation of IFPRS for a CE. A more systematic method and statistical confirmation is necessary to establish further new confronting issues. This study is limited to Indian manufacturing industries. Originality/value The main contribution of this study includes identification of issues and later prioritizing them to reflect their severity. This would help the industry practitioners to formulate strategies for handling the issues conveniently.
Keywords: 650; Circular economy; Fuzzy VIKOR; Information facilitated product recovery system; Multi criteria decision making